Formation Mechanism of Maghemite Nanoflowers Synthesized by a Polyol-Mediated Process - Gavilán, Helena; Sánchez, Elena H; Brollo, María E. F; Asín, Laura; Moerner, Kimmie K; Frandsen, Cathrine; Lázaro, Francisco J; Serna, Carlos J; Veintemillas-Verdaguer, Sabino; Morales, M. Puerto; Gutiérrez, Lucía (ACS omega, 2017)
Magnetic nanoparticles are being developed as structural and functional materials for use in diverse areas, including biomedical applications. Here, we report the synthesis of maghemite (γ-Fe2O3) nanoparticles with distinct morphologies: single-core and multicore, including hollow spheres and nanoflowers, prepared by the polyol process. We have used sodium acetate to control the nucleation and assembly process to obtain the different particle morphologies. Moreover, from samples obtained at different time steps during the synthesis, we have elucidated the formation mechanism of the nanoflowers: the initial phases of the reaction present a lepidocrocite (γ-FeOOH) structure, which suffers a fast dehydroxylation, transforming to an intermediate “undescribed” phase, possibly a partly dehydroxylated lepidocrocite, which after some incubation time evolves to maghemite nanoflowers. Once the nanoflowers have been formed, a crystallization process takes place, where the γ-Fe2O3 crystallites within the nanoflowers grow in size (from ∼11 to 23 nm), but the particle size of the flower remains essentially unchanged (∼60 nm). Samples with different morphologies were coated with citric acid and their heating capacity in an alternating magnetic field was evaluated. We observe that nanoflowers with large cores (23 nm, controlled by annealing) densely packed (tuned by low NaAc concentration) offer 5 times enhanced heating capacity compared to that of the nanoflowers with smaller core sizes (15 nm), 4 times enhanced heating effect compared to that of the hollow spheres, and 1.5 times enhanced heating effect compared to that of single-core nanoparticles (36 nm) used in this work.